2019
DOI: 10.1039/c9nr02729g
|View full text |Cite
|
Sign up to set email alerts
|

Superconducting boron doped nanocrystalline diamond on boron nitride ceramics

Abstract: In this work we have demonstrated the growth of nanocrystalline diamond on boron nitride ceramic. We measured the zeta potential of the ceramics to select the diamond seeds. Diamond was then grown on the seeded ceramics using a microwave chemical vapour deposition system. A clear difference was found between the samples which were seeded with nanodiamond and the ones not seeded before growth. Raman spectroscopy confirmed the excellent quality of the diamond film. Dielectric measurements showed an increase in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
16
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 59 publications
0
16
0
Order By: Relevance
“…102 Similar results have been seen for other surfaces like silicon dioxide, silicon, silicon carbide to name a few. The nanoseeding technique is now being routinely used to grow diamond on ceramics, 105,106 cutting tools [107][108][109][110] etc. Researchers have also used ND solutions for selective seeding using ink-jet style writing technology, [111][112][113][114] contact printing, 115 photolithography [116][117][118] or masking 116,119,120 to dene diamond structures without post diamond growth lithography and etching.…”
Section: Electrostatic Seedingmentioning
confidence: 99%
“…102 Similar results have been seen for other surfaces like silicon dioxide, silicon, silicon carbide to name a few. The nanoseeding technique is now being routinely used to grow diamond on ceramics, 105,106 cutting tools [107][108][109][110] etc. Researchers have also used ND solutions for selective seeding using ink-jet style writing technology, [111][112][113][114] contact printing, 115 photolithography [116][117][118] or masking 116,119,120 to dene diamond structures without post diamond growth lithography and etching.…”
Section: Electrostatic Seedingmentioning
confidence: 99%
“…Diamond, the hardest known material, has been attracting continuous interest for decades in cutting tools and applications in high-pressure science because of its excellent mechanical properties, high thermal conductivity and chemical stability. [1][2][3][4][5][6][7][8] However, the great challenge to shape, limited physical dimensions and high cost of nearly perfect singlecrystal (sc) diamonds have severely limited their widespread technological application in some extreme environments. In addition, previous studies have found that the inherent brittle strength would increase obviously with the increase of hardness of diamond.…”
Section: Introductionmentioning
confidence: 99%
“…The result is a decrease in the real part and a loss peak at the relaxation frequency of 1/τ . The h-BN samples are commercially obtained with details of the material synthesis detailed elsewhere 19 . Briefly, the hot-pressed h-BN substrates have approximate dimensions of 0.5 × 10 × 10 mm.…”
mentioning
confidence: 99%
“…Before CVD diamond growth a pre-baking stage was required for the substrates before diamond seeding using a hydrogen terminated colloid solution. After seeding, microwave plasma assisted CVD was carried out using a Seki Technotron AX6500 (4 kW at 50 Torr) in a 3% CH 4 / H 2 gas mixture 19 .…”
mentioning
confidence: 99%
See 1 more Smart Citation